The Effectiveness of WhatsApp Online Learning Using Media Animation Power Point on Student Learning Outcomes at SDN Genuksari 02 Semarang - Setiani, Nurul; Suyahmo, Suyahmo; Sunarso, Ali (Universitas Negeri Semarang, 2021)
The covid pandemic has caused changes online learning from home to prevent the spread of Covid 19. Teachers use the WhatsApp for learning. Learning by using online applications such as WhatsApp Messenger can increase collaboration in learning, share knowledge and useful information in the learning process, and maintain the joy of learning based on the ages. The purpose of this study was to analyze the effectiveness of student learning outcomes with WhatsApp online learning using audio-visual animation media in class IV theme 9 “Sub-Theme of Preserving Natural Resources Wealth in Indonesia” SDN Genuksari 02 Semarang. This type of research is quantitative with a quasi-experimental design. This study uses a pre-test-post-test non-equivalent control group design with two classes of research objects consisting of a control class. Learning in the experimental class uses whatsapp group with video animation media, and control class learning uses whatsapp group. The data analysis technique used pre-requisite test, the average similarity test, learning completeness test and t-test. The results of the study indicate that there is an effectiveness of WhatsApp groups with media animations on the learning outcomes of class IV students in the Sub-theme of Preserving Natural Resources Wealth in Indonesia at SDN Genuksari 02 Semarang. By conducting this research, it is expected to increase students' interests in education by providing a comfortable, interesting, and fun learning environment in creative learning models and learning media.